Railroads tracks across America - Mill Creek Entertainment; United States. War Department; Dan Dalton Productions (Golden Valley, MN Mill Creek Entertainment, 2011)
Thirty-six rail industry, War Department, and film industry-produced short films chronicle the development of the railroad industry in the U.S. from the first transcontinental line to modern diesel engines.
Disc 1. Wheels of progress -- A great railroad at work -- Desert empire -- The big train -- New horizons -- Troop train -- The passenger train -- This is my railroad -- At this moment -- Big trains rolling -- Mainline USA -- Beef rings the bell -- Safe roads -- 3rd Ave El -- Operation fast freight -- The modern coal burning steam locomotive -- Flight of the century -- Disc 2. The steam locomotive -- Railroads and westward expansion: 1845-1865 -- The nickel plate story -- End of an era -- The California Zephyr -- Return of the General -- The freight train -- Railroad man -- The railroad story -- Son of the pioneer -- Rolling the freight -- Snow on the run -- The power behind the nation -- Clear track ahead! -- A railroad at work -- Last of the giants -- Progress on the rails -- Wheels of steel -- Opening a new frontier.
Full screen (1.33:1).
Title from container.
"36 documentary collection"--Container
"A timeless journey riding the rails"--Container
Documentary film.
Exclusive featurette: America's railroad : the glory years.
Keywords: 1860-1921; Railroads -- United States -- History; United States -- History -- 1865-1921.; West (U.S.) -- History -- 1860-1890.; United States; West United States; Documentaries and Factual Films; Documentary films; Historical films; History; Nonfiction films; Short films